2012
DOI: 10.1108/09696471211239712
|View full text |Cite
|
Sign up to set email alerts
|

The role of facilitators in project action learning implementation

Abstract: PurposeThis paper addresses the importance of a more proactive role of organizational learning (OL) facilitators, learning motivation reinforcer, through a two‐part longitudinal study in a case company. The first part of this study aims to investigate and analyze some unexpected challenges in the project action learning‐driven (PAL) OL implementation in the case company, and the second part seeks to discuss an enhanced role of OL facilitators to cope with the new challenges.Design/methodology/approachA longitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 19 publications
(34 reference statements)
0
21
0
Order By: Relevance
“…That is, facilitation of learning (Ellinger and Bostrom, 1999;Cao et al, 2012). As facilitators of learning, managers are expected to coach employees by questioning their mental frame and encouraging them to think through issues; managers are also expected to promote a learning environment and to involve others to facilitate learning (Ellinger and Bostrom, 1999;Cao et al, 2012). As a consequence, it is not surprising that the positive outcomes identified in this study are not easy to sustain as dealing with lean paradoxes involves a continuous and lengthy learning process for both managers and employees.…”
Section: Managing Paradoxical Tensionsmentioning
confidence: 91%
See 1 more Smart Citation
“…That is, facilitation of learning (Ellinger and Bostrom, 1999;Cao et al, 2012). As facilitators of learning, managers are expected to coach employees by questioning their mental frame and encouraging them to think through issues; managers are also expected to promote a learning environment and to involve others to facilitate learning (Ellinger and Bostrom, 1999;Cao et al, 2012). As a consequence, it is not surprising that the positive outcomes identified in this study are not easy to sustain as dealing with lean paradoxes involves a continuous and lengthy learning process for both managers and employees.…”
Section: Managing Paradoxical Tensionsmentioning
confidence: 91%
“…As we attempted to make sense of this range of managerial responses and practices, we searched the extant learning literature and found that all these managerial practices share a common denominator. That is, facilitation of learning (Ellinger and Bostrom, 1999;Cao et al, 2012). As facilitators of learning, managers are expected to coach employees by questioning their mental frame and encouraging them to think through issues; managers are also expected to promote a learning environment and to involve others to facilitate learning (Ellinger and Bostrom, 1999;Cao et al, 2012).…”
Section: Managing Paradoxical Tensionsmentioning
confidence: 99%
“…In the facilitation literature, terms such as competences, dimensions, functions, and tasks [ 24 – 35 ] are used to describe expectations or what a facilitator should be doing. Role behaviors are described by using terms such as activities, actions, behaviors, interventions, or impact codes [ 3 , 5 , 25 , 29 , 30 , 36 – 40 ]. For this study, the term “role” is the most appropriate, as it encompasses observed behaviors as well as expectations related to EFs and IFTs.…”
Section: Introductionmentioning
confidence: 99%
“…A facilitator summarizes and analyzes training session results and presents their possible application by trainees. Therefore, facilitator forms and supports the efficient learning activity of the group of employees being trained (Cao, Chuah, Chau, Kwong & Law, 2012).…”
Section: Resultsmentioning
confidence: 99%